Case Report: Restrictive cardiomyopathy due to a rare mutation in troponin I gene (TNNI3) in a patient - Deng, Lili; Luo, Liming; Zhang, Min; Guo, Cheng; Liu, Kai (Frontiers in Cardiovascular Medicine, 2024)
BackgroundRestrictive cardiomyopathy (RCM) is a rare cardiomyopathy often characterized by normal or reduced ventricular chamber volume and bi-atrial enlargement, caused mainly by mutations in the myonodal gene. It has a low incidence, non-specific clinical manifestations, rapid progression, and lack of specific treatment, with heart transplantation usually being the ultimate treatment.Methods and resultsThis case reports a case of a 2-year-2-month-old boy located in Yunnan Province, China, who was admitted to the hospital with a 2-month history of orofacial bruising, aggravated by a 1-week history of bilateral eyelid swelling. After admission, electrocardiogram showed bi-atrial enlargement, echocardiography suggested bi-atrial enlargement with right and left ventricular diastolic hypoplasia, and cardiac magnetic resonance showed bi-atrial dilatation and possible localized myocardial fibrosis. A de novo heterozygous mutation (c.574C > T, p.Arg192Cys) in the TNNI3gene was identified by whole exome sequencing and verified by Sanger sequencing. The patient’s family opted for conservative treatment after diagnosis, but the patient died suddenly 2 months after diagnosis.ConclusionThis study identified a case of RCM due to TNNI3 mutation, emphasizing the importance of cardiac MRI and genetic testing in the clinical diagnosis of RCM and the need for heart transplantation. The study also revealed the possible heterogeneity of TNNI3 mutations across ethnic and geographic backgrounds, suggesting that long-term studies of genetic mutations should be strengthened in the future to promote the development of precision treatment strategies for cardiomyopathy.